2014
DOI: 10.1039/c3cp53440e
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic studies of the BrO + ClO cross-reaction over the range T = 246–314 K

Abstract: The kinetics of the atmospherically important gas phase radical reaction between BrO and ClO have been studied over the temperature range T = 246-314 K by means of laser flash photolysis coupled with UV absorption spectroscopy. Charge-coupled-device (CCD) detection allowed simultaneous monitoring of both free radicals and the OClO product using 'differential' spectroscopy, which minimised interference from underlying UV absorbing species. In this way, the total rate coefficient for BrO + ClO → products (1) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The apparatus for this radical generation and monitoring has been described in detail previously and its adoption here was identical to that employed in our recent studies of the ClO + HO 2 and ClO + BrO reactions. 5,20,21 Briefly, gas mixtures were prepared in a continuous flow of oxygen or synthetic air in a mixing line using calibrated mass flow controllers or PTFE needle valves. These gases (used as supplied, 499.9% purity) were flowed into a temperature controlled reaction cell and excimer laser photolysis was achieved by coupling laser output through cylindrical expansion lenses and dichroic reflectors longitudinally through the 1 metre long reaction cell.…”
Section: (Ii) Radical Generationmentioning
confidence: 99%
“…The apparatus for this radical generation and monitoring has been described in detail previously and its adoption here was identical to that employed in our recent studies of the ClO + HO 2 and ClO + BrO reactions. 5,20,21 Briefly, gas mixtures were prepared in a continuous flow of oxygen or synthetic air in a mixing line using calibrated mass flow controllers or PTFE needle valves. These gases (used as supplied, 499.9% purity) were flowed into a temperature controlled reaction cell and excimer laser photolysis was achieved by coupling laser output through cylindrical expansion lenses and dichroic reflectors longitudinally through the 1 metre long reaction cell.…”
Section: (Ii) Radical Generationmentioning
confidence: 99%
“…34,34,35 The experimental conditions chosen for the present study were similar, the only difference being the use of Cl 2 in the present work as an extra source of Br atoms via the reaction of Cl with Br 2 (8). Therefore the results of the current work are compared to the more comprehensive and extensive study of Ferracci et al 33 Figure 7(a) shows that the overall rate constant at T = 298 K obtained for reaction (3) However, the overall effect on the values of k 1 arising from these differences in approach appears to be small as indicated by their general agreement and the sensitivity parameters discussed above.…”
Section: Comparison With Previous Studiesmentioning
confidence: 94%
“…This enabled unequivocal determination of BrO concentrations at each time point, despite the presence of other absorbers, as has been demonstrated in our previous work. 33,34,35 The BrO reference spectra were taken from the work of Wilmouth et al 36 These crosssections are reported at higher spectral resolution (0.4 nm FWHM) than spectra recorded in the present study (1.1 nm FWHM), so a smoothing function using a…”
Section: Spectral Analysismentioning
confidence: 99%
See 1 more Smart Citation